Sintering properties and low-temperature degradation behaviour of Y-TZP ceramics - Ting, C.H.; Ramesh, S.; Lwin, N.; Sutharsini, U. (Hanyang University Press, 2016)
Y-TZP ceramics has outstanding mechanical properties and has been used for many engineering applications. However, a major drawback of this ceramic is the undesirable ageing-induced tetragonal to monoclinic phase transformation resulting in properties deterioration when exposed to steam environment. In the present work, the effect of sintering temperatures (1200 to 1500°C) on mechanical properties, microstructure and low temperature ageing behaviour of the sintered Y-TZP samples were investigated. The sintered bodies were characterized to determine the bulk density, Young’s modulus, Vickers hardness and fracture toughness. The sintered samples were exposed to superheated steam at 180°C/10 bar vapor pressure and the extent of monoclinic phase development were measured at selected intervals. It was found that the relative density and Young’s modulus of the sintered samples increased with sintering temperature and attained a maximum value of 99% and 211 MPa, respectively at 1400°C. On the other hand, maximum Vickers hardness and fracture toughness of 14.4 GPa and 5.07 MPam1/2 respectively, was measured at 1350°C. X-ray diffraction studies indicated that after 24 h of ageing, no traces of monoclinic phase was found in the Y-TZP having an average grain size of below 0.3 µm. The study found that sintering at 1350-1400°C was optimum to produce sintered bodies having good ageing resistant without sacrificing the mechanical properties.